Pengaruh kemoterapi neoadjuvant terhadap LMP1 dan rasio CD4+/CD8+ pada karsinoma nasofaring tak-berdiferensiasi - Sunardo Budi Santoso; Muhardjo M; Made Setiamika; Imam Prabowo; Dyah Ratna Budiani (Oto Rhino Laryngologica Indonesiana, 2012)
Background: Epstein-Barr virus (EBV) infection in undifferentiated type nasopharyngealcarcinoma (NPC) will express antigenic proteins such as LMP1 and triggering a cascade ofimmunocompetent cells (CD4+ and CD8+). The ratio of CD4+/CD8 illustrates the potential eliminationof intracellular pathogens and tumor cells. Neoadjuvant chemotherapy will suppress the growth of tumorcells and immune system cells   that leads to cellular immune decline. Objective: To know the influence ofneoadjuvant chemotherapy on the expression of LMP1, the immune system and the relationship betweenthe expression of LMP1 with the ratio of CD4+/CD8++. Method: The design was one group before andafter intervention, with 10 samples of undifferentiated NPC, biopsied before and after neoadjuvant chemotherapy, and got immunohistochemical examination. We used mouse antihuman LMP1, mouse monoclonal antihuman CD4+ and antihuman CD8 antibodies. Data were analyzed with the WilcoxonSigned Ranks test, and Spearman’s Linear Regression. Result: After neoadjuvant chemotherapy, we + found statistically significant decline in LMP1 expression (p = 0.007), CD4+ (p = 0.041) and CD8   (p= 0.005). The ratio of CD4+/CD8 increase was not statistically significant (p = 0.646). The relationshipbetween the expression of LMP1 with the ratio of CD4++/CD8was very weak (r = 0.17) and no statisticallysignificant (p = 0.646). Conclusion: Neoadjuvant chemotherapy in undifferentiated type NPC causes adecrease in the expression of LMP1 and immunological status (CD4 + +, CD8 ) and increase in the ratioof CD4+/CD8+. The relationship between the expression of LMP1 with the ratio of CD4+ was veryweak and not significant. Keywords: nasopharyngeal carcinoma, expression of LMP1, CD4+, CD8++/CD8, ratio of CD4,neoadjuvant chemotherapy.+++/CD8+  Abstrak :  Latar belakang: Infeksi Epstein-Barr virus (EBV) pada karsinoma nasofaring (KNF) jenis takberdiferensiasiakanmengekspresikan protein antigen antara lain LMP1 dan memicu hadirnyasel-selimunokompeten(CD4+ dan CD8+). Rasio CD4+/CD8 menggambarkan potensi eliminasi patogen intraseldan sel tumor. Kemoterapi neoadjuvant akan menghambat pertumbuhan sel tumor dan juga menghambatpembentukan sel-sel sistem imun tubuh sehingga berefek pada penurunan imunitas seluler. Tujuan:Mengetahui pengaruh kemoterapi neoadjuvant terhadap ekspresi LMP1, sistem imun dan hubunganantara ekspresi LMP1 dengan rasio CD4+/ CD8++. Metode: Desain penelitian one group before and afterintervention, menggunakan 10 sampel biopsi KNF tak-berdiferensiasi, sebelum dan sesudah kemoterapineoadjuvant dilakukan pemeriksaan imunohistokimia. Antibodi yang digunakan ialah antibodi mouseantihuman LMP1, monoclonal mouse antihuman CD4+ dan antihuman CD8. Data penelitian dianalisisdengan Wilcoxon Signed Ranks test, Regresi Linier dan Spearman’s dengan program statistik SPSS forWindows. Hasil: Setelah kemoterapi neoadjuvant terjadi penurunan signifikan secara statistik baikekspresi LMP1 (p=0,007); CD4+ (p=0,041), maupun CD8+ (p=0,005). Rasio CD4++/CD8 meningkat tidaksignifikan secara statistik (p=0,646).   Hubungan antara ekspresi LMP1 dengan rasio CD4 sangatlemah (r = 0,17) dan tidak signifikan secara statistik (p=0,646). Kesimpulan: Kemoterapi neoadjuvantpada KNF jenis tak-berdiferensiasi menyebabkan penurunan ekspresi LMP1 dan status imunologi(CD4+,CD8+) serta peningkatan rasio CD4+/CD8++++/CD8/CD8. Hubungan antara ekspresi LMP1 dengan rasio CD4/CD8 sangat lemah dan tidak signifikan. Kata kunci: karsinoma nasofaring, ekspresi LMP1, CD4++, CD8+, rasio CD4, kemoterapineoadjuvant.